Comparison Result of the Case of compressible Inviscid Flow Problem - Hasan Taher M.elkamel; Ir. Bambang Basuno; Mohammed Ahmed Alazhari; Elsalhin mispah Mohamed (Surman Journal of Science and Technology, 2020)
The present work presents a study of Two Dimensional Flow Analysis over NACA0012 and RAE2822 airfoils. here the aerodynamics analyses are carried out by use of Cell Centered Finite Volume scheme. Through this study, a grid generation algorithm has been developed to fulfill the need of the case of two dimensional C-topolgy. There are types of grid generator can be adopted: structured grid or unstructured grid. The first grid approach is normally needs less expenses compared to the second one. Using an ordinary approach in creating the grid of the flow domain by algebraic grid generation method The validation of the developed computer code carried out by comparing its result with Fluent software and experimental results, it had been found that some discrepancies result in term of Mach number or other flow properties between the developed computer code and fluent software are apparently. By improving grid of the flow domain by use of smoothing technique give the developed computer produce the result in a good agreement with the fluent software and the experimental result as well. Considering the ability of the developed computer code similar to the Fluent software, the present code had been used to evaluate the aerodynamics characteristics for other cases such as fuselages.